Appropriate use of antiplatelet medications following transient ischemic attacks and stroke: a 9-year study from the Middle East - Naveed, Hiba; Akhtar, Naveed; Al-Jerdi, Salman; Uy, Ryan Ty; Joseph, Sujatha; Morgan, Deborah; Babu, Blessy; Shanthi, Shobana; Shuaib, Ashfaq (Frontiers in Neurology, 2023)
Background and purpose: Guidelines recommend patients with high-risk TIAs and minor stroke presenting within 1-3 days from onset be offered dual antiplatelet therapy (DAPT). There is little data on real-world adherence to these recommendations. We evaluated the appropriateness of DAPT use in TIA and stroke patients in a prospective Database.The Qatar Stroke Database began enrollment of patients with TIAs and acute stroke in 2014 and currently has 16,000 patients. For this study, we evaluated the rates of guideline-adherent use of antiplatelet treatment at the time of discharge in patients with TIAs and stroke. TIAs were considered high-risk with an ABCD2 score of 4 and minor stroke was defined as NIHSS 3. Patient demographics, clinical features, risk factors, previous medications, imaging and laboratory investigations, final diagnosis, discharge medications, and discharge and 90-day modified Rankin Scale (mRS) were analyzed.After excluding patients with ICH, mimics, and rare secondary causes, 8082 patients were available for final analysis (TIAs: 1357; stroke 6725). In high-risk TIAs, 282 of 666 (42.3%) patients were discharged on DAPT. In patients with minor stroke, 1207 of 3572 (33.8%) patients were discharged on DAPT. DAPT was inappropriately offered to 238 of 691 (34.4%) low-risk TIAs and 809 of 3153 (25.7%) of non-minor stroke patients.This large database of prospectively collected patients with TIAs and stroke shows that, unfortunately, despite several guidelines, a large majority of patients with TIAs and stroke are receiving inappropriate antiplatelet treatment at discharge from the hospital. This requires urgent attention and further investigation.